Assessment of maximal fat oxidation during exercise: A systematic review. (21st April 2019) - Amaro‐Gahete, Francisco J.; Sanchez‐Delgado, Guillermo; Jurado‐Fasoli, Lucas; De‐la‐O, Alejandro; Castillo, Manuel J.; Helge, Jørn W.; Ruiz, Jonatan R.
Abstract : Maximal fat oxidation during exercise (MFO) and the exercise intensity eliciting MFO (Fatmax ) are considered biological markers of metabolic health and performance. A wide range of studies have been performed to increase our knowledge about their regulation by exercise and/or nutritional intervention. However, numerous data collection and analysis approaches have been applied, which may have affected the MFO and Fatmax estimation. We aimed to systematically review the available studies describing and/or comparing different data collection and analysis approach factors that could affect MFO and Fatmax estimation in healthy individuals and patients. Two independent researchers performed the search. We included all original studies in which MFO and/or Fatmax were estimated by indirect calorimetry through an incremental graded exercise protocol published from 2002 to 2019. This systematic review provides key information about the factors that could affect MFO and Fatmax estimation: ergometer type, metabolic cart used, warm‐up duration and intensity, stage duration and intensities imposed in the graded exercise protocol, time interval selected for data analysis, stoichiometric equation selected to estimate fat oxidation, data analysis approach, time of the day when the test was performed, fasting time/previous meal before the test, and testing days for MFO/Fatmax and maximal oxygen uptake assessment. We suggest that researchers measuring MFO and Fatmax should take into account these key methodological issues that can considerably affect the accuracy, validity, and reliability of the measurement. Likewise, when comparing different studies, it is important to check whether the above‐mentioned key methodological issues are similar in such studies to avoid ambiguous and unacceptable comparisons.